Controlled synthesis of highly multi-branched Pt-based alloy nanocrystals with high catalytic performance. Issue 13 (10th March 2016) - Kim, Yena; Kwon, Yongmin; Hong, Jong Wook; Choi, Bu-Seo; Park, Yangsun; Kim, Minjune; Han, Sang Woo
Abstract : The controlled synthesis of highly multi-branched Pt-based alloy nanocrystals with high catalytic performance was achieved through a facile solvothermal method. Abstract : Alloy nanocrystals (NCs) consisting of Pt and a 3d transition metal (M) have been of tremendous interest due to their prominent catalytic performance. To precisely compare the inherent catalytic function between PtM NCs with different M elements and thus to find an optimal combination, the availability of a synthesis method that provides exclusive control over the M element is highly desirable. In the present work, we developed a general solvothermal synthesis method for the preparation of highly multi-branched PtM (M = Co, Ni, and Fe) alloy NCs with similar branch dimensions, compositional ratios between Pt and M, and surface chemical environments, irrespective of the identity of M. Using the methanol oxidation reaction (MOR) as a model catalysis reaction, we found a correlation between the catalytic capabilities of the PtM NCs and the kind of the secondary metal. The MOR activity of the PtM NCs outperformed that of a benchmark Pt/C catalyst, and it distinctly depended on the identity of M. The enhanced catalytic function of the PtM alloy NCs compared to Pt/C can be attributed to their unique structural characteristics and the decrease in the binding energy of intermediates due to the synergism between Pt and M. Among the different PtM alloy NCs, the PtCo NCs exhibited the highest catalytic activity, stability, and CO tolerance due to the effective modification of their surface electronic structure. The present strategy can expand our opportunities for the rational design of advanced NC catalysts with controlled morphological, compositional, and electronic structures.